Uses for ruins: Anne Enright's The Green Road. Issue 1 (2nd January 2021) - Ryan, Matthew
ABSTRACT: Since her early work, Anne Enright has manipulated national and gender stereotypes in a knowing and sometimes playful way. This article focusses on the use of the well-worn Irish tropes of the mother and the family home as they appear in The Green Road . In particular, it considers the ways alternative historical and social possibilities are coded into cliché and stereotype. Rather than appearing as a linguistic limitation or an exhaustion of meaning these images and characterisations are pointing to unrealised cultural resources from the past. A recuperation of historical failure is enacted in Enright's use of these stereotypical forms. David Lloyd's Irish Times serves as an analytical model. Lloyd sees Irish landscapes and ruins as carriers of past failure but also of futures not yet achieved. Enright draws new meaning from old imagery, refashioning the ideas of the home for a critique of the present. This article reads The Green Road as a post-Celtic Tiger text that, in the evocation of cultural and physical impoverishment, brings a historical legacy to the critique of the recent global economic crisis and to neoliberal forms of value.